Reprogramming of IL-12 secretion in the PDCD1 locus improves the anti-tumor activity of NY-ESO-1 TCR-T cells - Kim, Segi; Park, Cho I; Lee, Sunhwa; Choi, Hyeong Ryeol; Kim, Chan Hyuk (Frontiers in Immunology, 2023)
Although the engineering of T cells to co-express immunostimulatory cytokines has been shown to enhance the therapeutic efficacy of adoptive T cell therapy, the uncontrolled systemic release of potent cytokines can lead to severe adverse effects. To address this, we site-specifically inserted the interleukin-12 (IL-12) gene into the PDCD1 locus in T cells using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)-based genome editing to achieve T-cell activation-dependent expression of IL-12 while ablating the expression of inhibitory PD-1. Using New York esophageal squamous cell carcinoma 1(NY-ESO-1) TCR-T cells as a model system, we showed that the endogenous PDCD1 regulatory elements can tightly control the secretion of recombinant IL-12 in a target cell-dependent manner, at an expression level that is more moderate than that obtained using a synthetic NFAT-responsive promoter. The inducible expression of IL-12 from the PDCD1 locus was sufficient to enhance the effector function of NY-ESO-1 TCR-T cells, as determined by upregulation of effector molecules, increased cytotoxic activity, and enhanced expansion upon repeated antigen stimulation in vitro. Mouse xenograft studies also revealed that PD-1-edited IL-12-secreting NY-ESO-1 TCR-T cells could eliminate established tumors and showed significantly greater in vivo expansion capacity than control TCR-T cells. Our approach may provide a way to safely harness the therapeutic potential of potent immunostimulatory cytokines for the development of effective adoptive T cell therapies against solid tumors.